A Case of Thoracic Extraspinal Extradural Tanycytic Ependymoma with Its Radiological and Histopathological Findings - Esmerer, Emel; Tekcan Şanlı, Deniz Esin; Kayadibi, Yasemin (Cerrahpaşa Medical Journal, 2022)
Extraspinal extradural tanycytic ependymoma is a very rare variant of ependymomas that usually tends to be localized in the spinal cord. We report a case of a 52-year-old woman presenting with back pain because of extraspinal extradural tanycytic ependymoma which is located in the paraspinal muscles at the level of the thoracic spine and presented its radiological and histopathological findings. Cite this article as: Esmerer E, Tekcan Şanlı DE, Kayadibi Y. A case of thoracic extraspinal extradural tanycytic ependymoma with its radiological and histopathological findings. Cerrahpaşa Med J. 2022;46(2):175-177.